Changes in Australians' attitudes towards supervised injecting facilities - Lloyd, Z.; Colledge-Frisby, Samantha; Taylor, Nicholas; Livingston, Michael; Jauncey, M.; Roxburgh, A. (2024)
Introduction: Supervised injecting facilities (SIF) have been shown to reduce negative outcomes experienced by people who inject drugs. They are often subject to intense public and media scrutiny. This article aimed to explore population attitudes to SIFs and how these changed over time in Australia. Methods: Data were drawn from the National Drug Strategy Household Survey, a national sample collecting data on illicit drug use and attitudes towards drug policy among Australians (2001–2019). Ordinal logistic regression assessed sociodemographic characteristics associated with different attitudes to SIFs and binary logistic regression assessed trends over time and by jurisdiction. Results: In 2019, 54% of respondents (95% CI 52.9, 55.1) supported SIFs, 27.5% (95% CI 26.6, 28.4) opposed and 18.4% (95% CI 17.7, 19.2) were ambivalent. Support for SIFs correlated with having a university degree (OR 1.75; 95% CI 1.58, 1.94), non-heterosexual identity (OR 1.81, 95% CI 1.51, 2.17) and recent illicit drug use (OR = 1.74, 95% CI 1.55, 1.94). Male respondents or those living in socioeconomically disadvantaged areas had lower odds of supporting SIFs (OR 0.92, 95% CI 0.85, 1.00; OR 0.64–0.80, respectively). Between 2001 and 2019, support for SIFs increased modestly by 3.3%, those who ‘don't know’ by 7.4%, whereas opposition decreased by 11.7%. Between 2001 and 2019, support for SIFs increased in NSW and Queensland, whereas opposition decreased in all jurisdictions. Discussion and Conclusions: Opposition to SIFs declined over the past 20 years, but a substantial proportion of respondents are ambivalent or ‘don't know enough to say’. Plain language information about SIFs and their potential benefits, targeted to those who are ambivalent/’don't know’ may further increase public support.